Enhancing MSME Competitiveness Through Halal Certification Assistance: A Case Study of Kampung Genteng Candirejo - Fani Khoirotunnisa; Amalya Diva Andriyani; Dini Talita Sari (Institut Riset dan Publikasi Indonesia, 2025)
The halal industry has experienced rapid global growth; however, Micro, Small, and Medium Enterprises (MSMEs) in Indonesia still face challenges in obtaining halal certification. Kampung Genteng Candirejo in Surabaya houses a Herbal Processing Center that has been operating since 2008, yet limited knowledge, technical support, and financial constraints hinder its MSME members from obtaining halal certification. This community service program aims to enhance MSME competitiveness by providing halal certification assistance, including training, technical guidance, and marketing strategies. The methodology involves education, certification registration assistance, and program monitoring and evaluation. The results indicate an increased understanding of halal certification standards among MSMEs and a rise in the number of MSMEs applying for certification. This initiative positively impacts MSME business sustainability and supports Indonesia’s vision of becoming a global halal industry hub.